2005
DOI: 10.1523/jneurosci.3690-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Serotonin Depletion Affects Reversal Learning But Not Attentional Set Shifting

Abstract: Recently, we have shown that serotonin (5-HT) depletion from the prefrontal cortex (PFC) of the marmoset monkey impairs performance on a serial discrimination reversal (SDR) task, resulting in perseverative responding to the previously correct stimulus (Clarke et al., 2004). This pattern of impairment is just one example of inflexible responding seen after damage to the PFC, with performance on the SDR task being dependent on the integrity of the orbitofrontal cortex. However, the contribution of 5-HT to other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
264
5
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(301 citation statements)
references
References 61 publications
(67 reference statements)
21
264
5
2
Order By: Relevance
“…For instance, in a previous study, we have shown that increases in noradrenergic neurotransmission in mPFC selectively facilitated ED set shifting Lapiz and Morilak 2006). By contrast, others have suggested that reversal learning may be modulated in OFC specifically by serotonergic neurotransmission (Clarke et al 2004;Clarke et al 2005;Clarke et al 2007). …”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…For instance, in a previous study, we have shown that increases in noradrenergic neurotransmission in mPFC selectively facilitated ED set shifting Lapiz and Morilak 2006). By contrast, others have suggested that reversal learning may be modulated in OFC specifically by serotonergic neurotransmission (Clarke et al 2004;Clarke et al 2005;Clarke et al 2007). …”
Section: Introductionmentioning
confidence: 74%
“…Reversal learning has been studied as a measure of cognitive flexibility in humans (Fellows and Farah 2003;Murphy et al 2002;Rogers et al 2000;Rolls et al 1994), nonhuman primates (Clarke et al 2004;Clarke et al 2005;Clarke et al 2007;Dias et al 1996;Lee et al 2007), and rats (Birrell and Brown 2000;Boulougouris et al 2007a;Boulougouris et al 2007b;Idris et al 2005;McAlonan and Brown 2003;van der Meulen et al 2007). Effective reversal learning involves a number of specific and distinct operations, including: 1) detection of the shift in contingency (i.e., "error detection"); 2) inhibition of the prepotent, previously learned positive response; 3) overcoming learned avoidance of the previously negative stimulus; and 4) acquisition of the new association.…”
Section: Discussionmentioning
confidence: 99%
“…Destruction of cortical serotonergic projections or depletion of 5-HT produced deficits in reversal learning, rather than cognitive set shifting (Clarke et al, 2005(Clarke et al, , 2007Nomura, 1992). Reversal learning appears to be related more to the function of orbitofrontal cortex rather than medial prefrontal cortex (Clarke et al, 2007;McAlonan and Brown, 2003).…”
Section: Discussionmentioning
confidence: 93%
“…This manipulation dramatically impairs the ability to inhibit responding to the previously rewarded stimulus, while not affecting the initial acquisition of a discrimination (Clarke et al, 2004(Clarke et al, , 2005(Clarke et al, , 2007. To explain this discrepancy, we must take into account three factors: (1) the method of depletion, (2) the extent to which the task depends on inhibitory control, and (3) the neural site of action of 5-HT.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, neuroimaging studies with human volunteers have shown particularly pronounced effects of ATD on the (dorso)medial PFC during cognitive performance (Cools et al, 2005a;Evers et al, 2005Evers et al, , 2006aTalbot and Cooper, 2006;Van der Veen et al, 2007). Conversely, the disinhibitory effects resulted from selective 5-HT depletion in the OFC (Clarke et al, 2004(Clarke et al, , 2005(Clarke et al, , 2007. Thus, 5-HT depletion may have different functional consequences depending on the extent of depletion, task demands and on the neural site of action (medial PFC vs OFC).…”
Section: Discussionmentioning
confidence: 99%